2019
DOI: 10.3390/su11061579
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Fraudulent Financial Statements for the Sustainable Development of the Socio-Economy in China: A Multi-Analytic Approach

Abstract: Identifying financial statement fraud activities is very important for the sustainable development of a socio-economy, especially in China’s emerging capital market. Although many scholars have paid attention to fraud detection in recent years, they have rarely focused on both financial and non-financial predictors by using a multi-analytic approach. The present study detected financial statement fraud activities based on 17 financial and 7 non-financial variables by using six data mining techniques including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 22 publications
0
22
0
4
Order By: Relevance
“…Supervised learning techniques were selected for analysis more than unsupervised ones, with 65% of the articles from US, China, Taiwan and Spain [10]. A considerable number of studies that analysed the performance of classifiers on FSF detection have shown that SVM [11,12,13,14,15], NN [16,17,18,19], DT [20,21] perform well in FSF detection/prediction.…”
Section: Related Researchmentioning
confidence: 99%
“…Supervised learning techniques were selected for analysis more than unsupervised ones, with 65% of the articles from US, China, Taiwan and Spain [10]. A considerable number of studies that analysed the performance of classifiers on FSF detection have shown that SVM [11,12,13,14,15], NN [16,17,18,19], DT [20,21] perform well in FSF detection/prediction.…”
Section: Related Researchmentioning
confidence: 99%
“…Consequently, even early studies (in 2012) examined CART for the FSFD problem and performed relatively well for this problem [32]. Furthermore, a most recent article used six different classifiers that one of them was the CART algorithm [83]. C4.5 algorithm operates as a decision tree classifier among ML/DM techniques.…”
Section: ) Technique Typesmentioning
confidence: 99%
“…Financial statements are the main reference point for investors, creditors and stakeholders in the decision-making process (Yao et al, 2019). Fraudulent financial reporting transactions have increased rapidly in recent years.…”
Section: Literature Reviewmentioning
confidence: 99%